2015
DOI: 10.1038/srep10867
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1 is Associated with Tumor Progression and Confers a Multi-Modality Resistance Phenotype in Pancreatic Cancer

Abstract: Caveolin-1 (Cav-1) is a 21 kDa protein enriched in caveolae, and has been implicated in oncogenic cell transformation, tumorigenesis, and metastasis. We explored roles for Cav-1 in pancreatic cancer (PC) prognostication, tumor progression, resistance to therapy, and whether targeted downregulation could lead to therapeutic sensitization. Cav-1 expression was assessed in cell lines, mouse models, and patient samples, and knocked down in order to compare changes in proliferation, invasion, migration, response to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
86
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(96 citation statements)
references
References 55 publications
7
86
2
1
Order By: Relevance
“…Non-caveolar Cav1 has been described to impact a variety of traits necessary for the progression of cancer. In prostate cancer cells, Cav1 influences JAK/STAT and Src signaling with high levels of Cav1 correlating with worse outcomes (58). Importantly, in these cells exposure to radiation or the chemotherapeutic agents, gemcitabine and 5-fluorouracil, results in enhanced levels of Cav1 (58).…”
Section: Ptdser Is Required For Caveolaementioning
confidence: 99%
“…Non-caveolar Cav1 has been described to impact a variety of traits necessary for the progression of cancer. In prostate cancer cells, Cav1 influences JAK/STAT and Src signaling with high levels of Cav1 correlating with worse outcomes (58). Importantly, in these cells exposure to radiation or the chemotherapeutic agents, gemcitabine and 5-fluorouracil, results in enhanced levels of Cav1 (58).…”
Section: Ptdser Is Required For Caveolaementioning
confidence: 99%
“…Similarly, Cav-1 protein was dysregulated in several other gastrointestinal cancers. Tumoral Cav-1 expression increased in cancers cells compared to their normal counterparts, whereas stromal Cav-1 expression decreased in cancer tissues compared to adjacent normal tissues, such as pancreatic cancer [9,19], esophageal cancer [20], and hepatocellular carcinomas [21]. Cav-1 expression is known to be regulated mainly by inactivation of oncogenes or inactivation of tumor suppressive genes, TGF-β, and oxidative stress in the tumor microenvironment [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have related Cav-1 overexpression with oncogenic transformation, invasion, and metastasis. Recently, Chatterjee et al have observed that CAV-1 knockdown reduced proliferative, invasive, and migratory properties in multiple pancreatic cancer cell lines [9]. Cav-1 affects several signaling pathways in cellular transformation, including aerobic glycolysis, JAK/STAT, JNK, and Src signaling pathway [9,28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations